Stunting Prevention of Elementary School Children Based on Nutrition Education Peer Group: A Quasy Experimental - Nurhalimah Batubara; Yuli Arisyah Siregar; Anto J. Hadi; Haslinah Ahmad; Adi Antoni; Abdullah A.A (Journal of Public Health and Pharmacy, 2025)
Introduction: Stunting in elementary school children is a nutritional problem that impacts physical and cognitive development. One of the main factors causing stunting is the lack of knowledge, attitudes, and appropriate actions in maintaining children's nutrition. Objective: This study aims to evaluate the effectiveness of peer group-based nutrition education in preventing stunting in elementary school children. Methods: A type of quantitative research with a quasi-experimental design with experimental and control groups in two primary schools. The sample was selected by purposive sampling consisting of a treatment group and a control group of 30 samples each. The intervention was carried out for three months and was carried out in 6 meeting sessions for 3 weeks. Each session is held for 60 minutes and is guided by a facilitator who is trained through a nutrition education program carried out by peer students with materials that include the importance of nutritious diets, healthy living behaviors, and stunting with the media of nutrition posters and leaflets, every month children are monitored using modified food recalls. Data were analyzed using paired t-test and chi-square test to compare the difference before and after the intervention. Results: This study found a significant improvement in nutrition-related knowledge, attitudes, and actions in the experimental group compared to the control group (p=0.001<0.05). Conclusion: This study proves that peer group-based nutrition education programs effectively increase knowledge, attitudes, and actions that can prevent stunting in elementary school children. Based on these findings, it is recommended to expand the application of similar interventions in schools to reduce the prevalence of stunting.